Fluorescence‐detected quick‐scanning X‐ray absorption spectroscopy. (6th April 2020) - Clark, Adam H.; Steiger, Patrick; Bornmann, Benjamin; Hitz, Stephan; Frahm, Ronald; Ferri, Davide; Nachtegaal, Maarten
Abstract : Application of time‐resolved fluorescence‐detection quick X‐ray absorption spectroscopy using a partially depleted passivated implanted planar silicon detector at the SuperXAS beamline. Abstract : Time‐resolved X‐ray absorption spectroscopy (XAS) offers the possibility to monitor the state of materials during chemical reactions. While this technique has been established for transmission measurements for a number of years, XAS measurements in fluorescence mode are challenging because of limitations in signal collection as well as detectors. Nevertheless, measurements in fluorescence mode are often the only option to study complex materials containing heavy matrices or in samples where the element of interest is in low concentration. Here, it has been demonstrated that high‐quality quick‐scanning full extended X‐ray absorption fine‐structure data can be readily obtained with sub‐second time resolution in fluorescence mode, even for highly diluted samples. It has also been demonstrated that in challenging samples, where transmission measurements are not feasible, quick fluorescence can yield significant insight in reaction kinetics. By studying the fast high‐temperature oxidation of a reduced LaFe0.8 Ni0.8 O3 perovskite type, an example where the perovskite matrix elements prevent measurements in fluorescence, it is shown that it is now possible to follow the state of Ni in situ at a 3 s time resolution.